The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.3390/polym11030403
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Pressures of Supercritical Carbon Dioxide on the Microstructure of PAN Fibers during the Hot-Drawing Process

Abstract: The hot-drawing process of polyacrylonitrile (PAN) fibers is an important step during the production of PAN-based carbon fibers. In this study, supercritical carbon dioxide (Sc-CO2) was used as one kind of media for thermal stretching of PAN fibers to study the effect of different pressures of Sc-CO2 on crystallinity, degree of orientation and mechanical property of PAN fibers during the hot-drawing process. The changes of microstructure and mechanical properties in the PAN fibers were investigated by wide-ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…In conclusion, the articles published in this special issue, and reported above, confirmed the interesting peculiarities of supercritical fluids, i.e., SC-CO 2, that allow to improve the traditional processes performance [1,2,3,9] and the characteristics of a large number of polymers [4,5,6,7,8].…”
supporting
confidence: 66%
See 2 more Smart Citations
“…In conclusion, the articles published in this special issue, and reported above, confirmed the interesting peculiarities of supercritical fluids, i.e., SC-CO 2, that allow to improve the traditional processes performance [1,2,3,9] and the characteristics of a large number of polymers [4,5,6,7,8].…”
supporting
confidence: 66%
“…This special issue currently consists of a total of nine articles written by research groups of experts in the field. The papers can be substantially divided into two main topics:polymeric structure (nanoparticles, microparticles, foams) formation [1,2,3], useful for drug release applications;effects of supercritical fluids on polymer characteristics [4,5,6,7,8]. …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Luo studied the surface modification of aramid fiber in scCO 2 with glycidyl-POSS to improve the surface adhesion of aramid fiber/epoxy resin [29]. We reported a method the hot stretching and cyclic reaction of polyacrylonitrile (PAN) fibers in scCO 2 by controlling the temperature and tension to improve the mechanical properties or reduced the heat of the cyclic reaction [20,30]. In our earlier study, we reported a new method improving the mechanical properties of single aramid filament by forming a crosslinking network structure in the amorphous phase of a PPTA fiber with the aid of scCO 2 , which enhanced the amorphous phase and improved the tensile strength and modulus of the fiber [31].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Hobbs et al used the Sc-CO 2 as a reversible plasticizer, transport, and extraction medium to study the crystal annealing of commercial nylon-66, polyethylene terephthalate, and ultra-high molecular weight polyethylene fibers, respectively, during the post-treatment process, which showed that an increase in the modulus and toughness was achieved in nylon-66 [17]. Furthermore, Qiao et al used the Sc-CO 2 to induce the crystallization of polyacrylonitrile fibers, which showed that the crystallinity and mechanical properties of polyacrylonitrile fibers were improved after hot-drawing treatment [18].…”
Section: Introductionmentioning
confidence: 99%